Analisis Analisis Dan Perancangan Sistem Kredit Point Menggunakan Metode Ooad (Study Kasus Ma Dan Mts Taklimus Shibyan) - Jasri, Moh.; Fuadz Hasyim; Nafilatul Azizah (Universitas PGRI Kanjuruhan Malang, 2023)
The system for recording violation points and student achievement points at MTs and MA Taklimus Shibyan is currently not well integrated. Because the bookkeeping of violation points and achievements are in different ledgers. Credit Point calculation errors will have an impact on the score on the selection of the Student Star award candidate at every turn of the semester. With the Analysis and Design of a Student Credit Point Information System at MTs and MA Taklimus Shibyan, it is hoped that it can provide an overview of the Credit Point application that will make it easier for students to recap student Credit Points and determine student stars easily. Credit points are an installment system for recording violation points and achievement points to measure student discipline and non-discipline in facilitating school students in choosing class stars each semester. In this research, the system development method uses the OOAD (Oriented Object Analysis and Design) method. To make it easier for users to understand the designs made by researchers. So it is more efficient and easy. Based on the analysis and trials that have been carried out, it can be concluded that this research has resulted in the design of a Credit Point Information System for MA and MTs Taklimus Shibyan Students using the OOAD (Oriented Object Analysis and Design) method in accordance with the credit point rules in MA and MTs Taklimus Shibyan. Â